Reflections on Post-Conflict: Learning History - Romero Ospina, Fernando Arturo (2016)
This essay intends to reflect on how to make the learning of the political history of Colombia at school in the post-conflict scenario to encourage a reconciliation process. To do this, we will see how history has had various definitions which have been present in the school teaching fulfilling a social and political role in the construction of an identity and official memory. However, in the post conflict scenario, the school, as a socially recognized center, must facilitate a process of revision of the history of Colombian society to understand the events and origins of the current conflict so that a lasting reconciliation allows the actors of the conflict to express their points of view, and the effects of war do not cause a new conflict.